MULTIPLE-ACCESS TECHNOLOGY OF CHOICE IN 3GPP LTE - Frank, Ibikunle; Ike, Dike; Jimi, Ajayi; Kayode, Onasoga (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Third-Generation Partnership Project (3GPP) standardizes an Evolved UMTS Terrestrial Radio Access Network (EUTRAN) as air interface in its release 8 LTE. Orthogonal Frequency Division Multiple Access(OFDMA) and Single Carrier- Frequency Division Multiple Access(SC-FDMA)are key technologies for the air interface of mobile broadband systems.It isÂ evident that mobile broadband access technologies are reaching a commonality in the air interface and networkingÂ architecture; they are being converged to an IP-based network architecture with OFDMA based air interface technology.Â The air interface of E-UTRAN is based on OFDMA in downlink and SC-FDMA in the uplink, making it possible to efficientlÂ utilize bandwidth due to the orthogonally between sub-carriers and by assigning subsets of sub-carriers to individual usersÂ which allows for simultaneous data rate transmission from several users and differentiated quality of service for each user.Â In this paper, wehighlight the technologies behindOFDMA and SC-FDMA and also carry out performance comparison ofÂ the two air interface technologies. We brieflydescribe the 3GPP LTE standard, and its implementation using OFDMA andÂ SC-FDMA technology.